The Charter of the City of Newport, Rhode Island and the Special State Laws Relating Thereto, Together with the Ordinances for the Government of the City 39, § 11 (1858) - (:unkn) unknown (My University, 1822)
An Act providing in case of fire breaking out in the town of Newport an for the purposes therein mentioned, § 11: That no person whosoever shall fire a gun or other fire-works within one hundred yards of the said powder-house, upon the penalty of two dollars for every such offence, to be recovered by the town treasurer for the use of said town.
Keywords: DISCHARGE